PERAN TNI ANGKATAN DARAT DALAM MEMBANGUN KETAHANAN KELUARGA (STUDI KASUS PERUMAHAN SOKOWATEN SOROWAJAN BARU BANGUNTAPAN BANTUL YOGYAKARTA) - Kamilia, Nur (Al-Usroh : Jurnal Hukum Keluarga Islam, 2024)
Every individual is no exception in the household life of TNI members, that is they can build a harmonies family if they properly understand the role of each member of the family in the midst of their busy lives as civil servants and other profession, which is not an obstacle to running away from their role. What must be done for the resilience of a family. Families or individuals who are able to survive all existing conditions have the opportunity to have strong family resilience. The research method used is qualitative-descriptive, with data collection techniques in three ways, namely observation, interviews, and documentation. The result of this paper is more or less the discovery of several important roles played by the TNI AD and his wife in building household resilience, namely: 1. Good communication between husband and wife. 2. Share roles. 3. Mutual trust. 4. Vacation together or spending time with family. 5. Good communication with extended family and with in-laws. 6. Cultivate a sense of responsibility to children, especially to boys. 7. Applying authoritarian and democratic parenting. 8. Changing the role of the husband. 9. Take the wife wherever the husband is on duty. 10. Accompany my husband wherever he changes his job. With this, it is hoped that the TNI AD family will pay more attention to their role as family members so that they can build family resilience to build national resilience.